The Influence of B2B (Business to Business) and B2C (Business to Customer) Marketing Strategies on How to Purchase Lion Group Aircraft Tickets in The Public Environment - Rizky, Harry (International Journal Labs, 2023)
Airfare is a form of agreement between the buyer of flight services and the airline. Ticket sales are the biggest income for an airline company engaged in civil aviation. Airline companies will certainly carry out various strategies to support the marketing of their products. Including the use of B2B and B2C marketing strategies. Airline ticket sales are spread in various ways, either by buying from airlines directly by ordering through the company's website or the company's ticketing office through airline ticket sales agents or through airline ticket sales applications. This study aims to determine whether there is an influence of B2B and B2C marketing strategies on how to purchase airplane tickets in student circles. This research was conducted at the Ticketing Office of PT. Lion Group. This study uses primary data obtained directly from respondents by distributing 100 questionnaires. Questionnaires that have been collected are then analyzed. The results showed that the null hypothesis was accepted, namely, B2B and B2C marketing strategies simultaneously had no significant effect on the method of purchasing airplane tickets in student, office, and community environments with an F significance value of 0.340 which is above the significance level (?) of 0.05. Testing the coefficient of determination shows that R2 is worth 0.009, which means that the influence of B2B and B2C marketing strategies on how to buy airplane tickets in student environments is only 0.9%. While 99.1% is influenced by other variables not discussed in this study.